2020
DOI: 10.3389/fimmu.2020.01437
|View full text |Cite
|
Sign up to set email alerts
|

Babesia microti Protein BmSP44 Is a Novel Protective Antigen in a Mouse Model of Babesiosis

Abstract: Babesiosis caused by Babesia species imposes an increasing threat to public-health and so far, there is no effective vaccine to prevent Babesia infections. Babesia surface antigen may participate in the invasion of erythrocytes. In our previous study, a surface antigen of B. microti merozoites, named as Bm SP44 was identified as a dominant reactive antigen by protein microarray screening. To evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Hb concentration, body weight and body temperature are indicators that reflect the severity of the disease, and they may be distinctly different when obvious protections are induced in the immune group [ 23 ]. In this study, we found that Hb concentration was significantly higher in the immune group than in the control group at days 3 and 6 after passive immunity regarding Bm infection.…”
Section: Discussionmentioning
confidence: 99%
“…Hb concentration, body weight and body temperature are indicators that reflect the severity of the disease, and they may be distinctly different when obvious protections are induced in the immune group [ 23 ]. In this study, we found that Hb concentration was significantly higher in the immune group than in the control group at days 3 and 6 after passive immunity regarding Bm infection.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous proteome high-throughput screening, some B. microti proteins with high antigenicity were identi ed [18,19]. The protection and diagnostic potential of one secreted protein BmSP44 was evaluated [20]. Bioinformatics analysis showed that an erythrocyte membrane associated protein8 of B. microti (named as Bm8 in this study) was conserved among the apicomplexa parasites such as Plasmodium spp.…”
Section: Introductionmentioning
confidence: 90%
“…Mice immunized with BmSP44 demonstrated a significant difference in parasitemia when compared to the control group. Nevertheless, both vaccinated and control group mice still experienced high peak parasitemia [ 47 ].…”
Section: Advances In B Microti Vaccine Developmentmentioning
confidence: 99%